Digital Transformation in Banking Services: The Impact of Mobile Banking on Customer Satisfaction at Islamic Banks in Tasikmalaya City - Mulyati, Sri; Septiani, Nendah; Marlina, Lina (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
This study aims to analyze the impact of mobile banking services on customer satisfaction at Bank Syariah Indonesia in Tasikmalaya City. The methodology applied is descriptive and verification based in a quantitative form. The study sample was determined using the Slovin method, involving a number of respondents who are customers of Bank Syariah Indonesia in the specified area. Data collection was conducted through literature review and questionnaires. To analyze the effect of mobile banking services on customer satisfaction, this study utilizes simple linear regression analysis with a set significance level. The analysis results indicate that mobile banking services have a positive and significant impact on customer satisfaction. Based on the coefficient of determination test, it was found that a majority of the variation in customer satisfaction can be explained by the use of mobile banking services, while the remaining portion is influenced by other factors not examined in this study. The statistical test results support a positive and significant effect between mobile banking services and customer satisfaction, reinforcing the relevance of these services in enhancing customer satisfaction at Bank Syariah Indonesia in Tasikmalaya City. The implications of continuous development of BSI Mobile enhances customer loyalty, strengthens competitiveness, and maintains Bank Syariah Indonesia's position amidst digital competition.